Decision Rules in Cost-Utility Analysis of Health Technologies - SAENGOW, Udomsak (Walailak Journal of Science and Technology (WJST), 2021)
This review identified 4 distinct decision rules used in the cost-utility analysis of health technologies: threshold incremental cost-effectiveness ratio (ICER), league table, decision making (DM) plane, and linear programming. The threshold ICER is currently the most widely-used approach. However, it comes with certain disadvantages: unrealistic assumptions (perfect divisibility and constant return to scale), arbitrarily-set threshold, and ignorance of opportunity cost. League table involves comparison of several health technologies simultaneously. The issue related to comparability between evaluation of each health technology limits its application. DM plane ensures improvement in health and sufficient resources mostly by disinvestment of currently funded programs. Its major disadvantages are difficulties in identification and disinvestment of such programs. Linear programming is, in theory, the best approach. Ideally, it requires sufficient data from all currently-funded or potential health technologies in conducting the analysis. Hence, the approach is somewhat impractical. Ongoing development in the field of data science and increasing availability of big data might enable its application in the near future. Given the mentioned shortcomings, pragmatic applications of league table and DM plane use them to evaluate competitive treatment programs for single health conditions. Using linear programming in prioritizing health programs was proven possible at the district level.